2010
DOI: 10.1016/j.cpr.2009.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of attentional biases towards threat in anxiety disorders: An integrative review

Abstract: A wealth of research demonstrates attentional biases toward threat in the anxiety disorders. Several models have been advanced to explain these biases in anxiety, yet the mechanisms comprising and mediating the biases remain unclear. In the present article, we review evidence regarding the mechanisms of attentional biases through careful examination of the components of attentional bias, the mechanisms underlying these components, and the stage of information processing during which the biases occur. Facilitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

68
1,164
11
17

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 1,449 publications
(1,299 citation statements)
references
References 139 publications
68
1,164
11
17
Order By: Relevance
“…This is consistent with the idea that visual attentional biases are linked to motivational systems (Mogg, Bradley, Miles & Dixon, 2004). Indeed, phobias have been linked with patterns of 'vigilance' and 'avoidance' toward threat-related stimuli (see Cisler & Koster, 2010 for review), and in adult populations research has consistently found strong associations between biases toward threatening visual stimuli (i.e. vigilance) and levels of anxiety (MacLeod, Matthews & Tata, 1986;Mogg, Holmes, Garner & Bradley, 2008), levels of attachment insecurity (Dewitte & De Houwer, 2008) and low self-esteem (Dandeneau, Baldwin, Baccus, Sakellaropoulo & Pruessner, 2007).…”
Section: Introductionsupporting
confidence: 86%
“…This is consistent with the idea that visual attentional biases are linked to motivational systems (Mogg, Bradley, Miles & Dixon, 2004). Indeed, phobias have been linked with patterns of 'vigilance' and 'avoidance' toward threat-related stimuli (see Cisler & Koster, 2010 for review), and in adult populations research has consistently found strong associations between biases toward threatening visual stimuli (i.e. vigilance) and levels of anxiety (MacLeod, Matthews & Tata, 1986;Mogg, Holmes, Garner & Bradley, 2008), levels of attachment insecurity (Dewitte & De Houwer, 2008) and low self-esteem (Dandeneau, Baldwin, Baccus, Sakellaropoulo & Pruessner, 2007).…”
Section: Introductionsupporting
confidence: 86%
“…Attentional avoidance is recognized to be a strategy actively employed at later stages of cognitive processing (e.g., from approximately 500 ms onwards after stimulus onset; e.g., Hofmann, Ellard, & Siegle, 2012) that works to regulate negative affect (Cisler & Koster, 2010). While we include theories and research that incorporate the notion of attentional avoidance, this concept is not central to our discussion of anxiety and attention.…”
Section: Empirical Evidence For Selective Attention To Threat In Anxietymentioning
confidence: 99%
“…It is possible that the avoidance tendencies of parents with heightened catastrophic thought may conflict with or be compromised by increased difficulty disengaging from pain in highly threatening or distressing situations [15,21,38,71].…”
Section: " "mentioning
confidence: 99%